Peacekeepers: Internationalist Protectors or National Perpetrators, Protected Either Way?. (10th December 2020) - Cryer, Robert; Perova, Natalia
Abstract: Peacekeepers occupy a liminal legal position, having never been provided for in the UN Charter. That said, a detailed legal regime has grown up around peacekeepers, both in terms of how they are protected by the criminal law and the jurisdictional regime that surrounds them. The piece argues that this relates to two sides of protection, which reflects dual image that has arisen around them. The first is that of international 'saviours' acting on behalf of a purported international community who have little more power than their moral authority, and therefore are worthy of additional protection from criminal law. This is shown through an analysis of the 1994 Convention on the Safety of United Nations and Associated Personnel and the relevant provisions of the Rome Statute of the International Criminal Court. However, peacekeepers have also been accused, of, and committed various crimes against the populations they are sent to protect. When this occurs, international law enters at a different level, casting peacekeepers as nationals of their sending State and placed in a jurisdictional regime that functionally, if not by design, protects 'our boys' from facing criminal liability for their conduct. This is investigated through analysis of peacekeepers' Status of Forces Agreements and the Rome Statute regime applicable to them. These deeply inconsistent narratives, of peacekeepers as representatives of international good intentions, and national actors, operate in tandem to shield them from the consequences of their conduct. We recommend a holistic approach that is understanding, but less forgiving.